PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA HOTEL MONA PLAZA PEKANBARU - Dahliyana, Dahliyana; Suryalena, Suryalena (Komunitas Manajemen Kompetitif, 2025)
Abstract: This study aims to determine the effect of organizational culture on employee job satisfaction at the Mona Plaza Hotel Pekanbaru. The independent variables consist of organizational culture (X1) and work environment (X2). While the dependent variable is job satisfaction (Y). This study uses a questionnaire with a measurement scale using a Likert scale. The analysis techniques used are simple linear regression, multiple linear regression, coefficient of determination test, hypothesis test. Data analysis uses linear regression analysis with the help of SPSS. The population in the study were 33 employees of the Mona Plaza Hotel Pekanbaru, all of whom were sampled using the census/total sampling technique. The results of the tests carried out showed that organizational culture and work environment have a positive influence on employee job satisfaction at the Mona Plaza Hotel Pekanbaru. Keywords: Organizational Culture, Work Environment, Job Satisfaction